1980
DOI: 10.1111/j.1532-950x.1980.tb01660.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarticular Allogeneic Bone Grafting in Dogs

Abstract: A review of the clinical and pathologic evaluation of allogeneic bone grafts is presented with particular emphasis upon partial joint replacement. The histologic evaluation of cortical bone transplantation is reviewed. Radiographic evaluation of cortical bone transplants is presented in an attempt to understand the normal events that take place in incorporation of the graft by the host. The histologic and radiographic correlation is related to the healing process. Current methods of graft collection and storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Herndam and Chase (1974) (cited by Enneking and Morris 1972), in an experimental study using dogs, demonstrated that the apposition of new bone commences two weeks post transplantation and although the total replacement of the graft takes nine to 12 months, it is indistinguishable radiographically at five months post surgery. Our observations of early radiographic evidence of new bone formation, present six weeks post surgery, are consistent with the findings in dogs by Helphrey and Stevenson (1980).…”
Section: Discussionsupporting
confidence: 91%
“…Herndam and Chase (1974) (cited by Enneking and Morris 1972), in an experimental study using dogs, demonstrated that the apposition of new bone commences two weeks post transplantation and although the total replacement of the graft takes nine to 12 months, it is indistinguishable radiographically at five months post surgery. Our observations of early radiographic evidence of new bone formation, present six weeks post surgery, are consistent with the findings in dogs by Helphrey and Stevenson (1980).…”
Section: Discussionsupporting
confidence: 91%